Perancangan Sistem Informasi Tindakan Operasi Guna Mengelola Laporan 10 Besar Tindakan Berbasis Elektronik - Zilvia, Leziza; Syahidin, Yuda; Sari, Irda (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The rapid development of technology is certainly very helpful for employee performance and services in hospitals, one of which is in the medical record installation, namely in the reporting of inpatient operations that have not been fully computerized. Problems were found during the Field Work Practice, one of which was the delay in the process of collecting patient surgery data, which made reporting hampered and did not run smoothly and efficiently. Therefore, an information system is needed to streamline employee performance in reporting complete, fast, and accurate operations. The research data collection methods used are literature study and interviews, with descriptive analysis. The method of making the system is using the waterfall method. It is hoped that the results of the design of this information system can streamline the performance of doctors, as well as officers in making reports on the top 10 index of surgical actions so as to produce complete and accurate data. And this information system can also maximize the quality of service in the hospital.